GazeAlyze: a MATLAB toolbox for the analysis of eye movement data - Berger, Christoph; Lischke, Alexander (Behavior research methods, 2011)
This article presents GazeAlyze, a software package, written as a MATLAB (MathWorks Inc., Natick, MA) toolbox developed for the analysis of eye movement data. GazeAlyze was developed for the batch processing of multiple data files and was designed as a framework with extendable modules. GazeAlyze encompasses the main functions of the entire processing queue of eye movement data to static visual stimuli. This includes detecting and filtering artifacts, detecting events, generating regions of interest, generating spread sheets for further statistical analysis, and providing methods for the visualization of results, such as path plots and fixation heat maps. All functions can be controlled through graphical user interfaces. GazeAlyze includes functions for correcting eye movement data for the displacement of the head relative to the camera after calibration in fixed head mounts. The preprocessing and event detection methods in GazeAlyze are based on the software ILAB 3.6.8 Gitelman (Behav Res Methods Instrum Comput 34(4), 605-612, 2002). GazeAlyze is distributed free of charge under the terms of the GNU public license and allows code modifications to be made so that the program's performance can be adjusted according to a user's scientific requirements.
Gesehen am 26.04.2018